Penentuan Umur Optimal Peremajaan Kelapa Sawit di Kabupaten Paser Kalimantan Timur - Mariyah, Mariyah; Syaukat, Yusman; Hartoyo, Sri; Fariyanti, Anna; Krisnamurthi, Bayu (Jurnal Ekonomi Kuantitatif Terapan, 2018)
Determining of optimal replanting age of oil palm helps farm households to prepare replanting investment. This research was to detemine optimal age for replanting of oil palm and to evaluate the sensitivity of optimal replanting age when there are changes in output price, cost, interest rate, and yield. The number of samples  are 268 oil palm farm household. The farmers, age of oil palm and location were taken based on purposive sampling. Data were analyzed using profit maximization concept with Comparison of Equivalent Annual Net Revenue (CEAN) method.  The result showed that the optimal replanting age of oil palm with quadratic production function  and cubic production function was between 33 and 35 years. The optimal replanting age was sensitive to changes on interest rate, price of fresh fruit bunch, farm cost, and productivity.